IMPLEMENTASI PROGRAM PERCEPATAN PENGANEKARAGAMAN KONSUMSI PANGAN (P2KP) PADA KELOMPOK WANITA TANI DI KELURAHAN LEMPAKE KECAMATAN SAMARINDA UTARA - Ariyadi Ariyadi (Jurnal Administrative Reform, 2020)
The purpose of this research is to describe and analyze the implementation of the acceleration of food consumption diversification (P2KP) program on the Women Farmers Group in Lempake Village, to identify and describe the supporting and inhibiting factors. This type of research is descriptive with a qualitative approach. The research location is in Lempake Sub-District, North Samarinda District. Data derived from interviews, observations and documents owned by farmer women's groups. Conclusions based on data processed using interactive model data analysis. Based on the results of the study, it was concluded that the implementation of the acceleration program of food consumption diversification (P2KP) on the women farmer groups in Lempake Village had been going well, although there were still things that needed improvement.Keywords: Implementation, Diversification,  Food Consumption